1993
DOI: 10.1055/s-2007-1002043
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Parathyroid Hormone-Related Protein (PTHrP) in Hypercalcemia of Malignancy Are not Lowered by Treatment With the Bisphosphonate BM 21.0955

Abstract: Parathyroid hormone-related protein (PTHrP) is a major cause of hypercalcemia in malignancy and serum levels are elevated in many patients suffering from this syndrome. In 10 patients with hypercalcemia of malignancy the levels of the midregional fragment of PTHrP in serum were determined by radioimmunoassay over 7 days during a calcium-lowering treatment with a single dose of the bisphosphonate BM 21.0955. PTHrP concentrations remained unchanged 6 days after administration of the drug as compared with prether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 14 publications
0
3
1
1
Order By: Relevance
“…Time to relapse was shorter in patients with high PTHrP levels than in patients with low levels. Considering PTHrP is accompanied by enhancement of kidney re-absorption of calcium and activation of osteoclasts, the higher proportion of patients with high PTHrP levels in our study may explain the shorter time to relapse and CR duration compared with the study by Major et al It is also noteworthy that the calcium-lowering effect of zoledronic acid 4 mg was retained even if patients had an elevated PTHrP level; nevertheless, it was reported that bisphosphonates such as pamidronate and ibandronate were less effective in reducing the serum calcium level in patients who had a higher PTHrP level (6)(7)(8)(9)(10). This important property is presumably due to the more potent pharmacological activity of zoledronic acid.…”
Section: Safetycontrasting
confidence: 48%
“…Time to relapse was shorter in patients with high PTHrP levels than in patients with low levels. Considering PTHrP is accompanied by enhancement of kidney re-absorption of calcium and activation of osteoclasts, the higher proportion of patients with high PTHrP levels in our study may explain the shorter time to relapse and CR duration compared with the study by Major et al It is also noteworthy that the calcium-lowering effect of zoledronic acid 4 mg was retained even if patients had an elevated PTHrP level; nevertheless, it was reported that bisphosphonates such as pamidronate and ibandronate were less effective in reducing the serum calcium level in patients who had a higher PTHrP level (6)(7)(8)(9)(10). This important property is presumably due to the more potent pharmacological activity of zoledronic acid.…”
Section: Safetycontrasting
confidence: 48%
“…PTHrP binds to the PTH receptor leading to osteoclastic bone resorption, increased resorption of calcium by the kidneys and renal phosphate loss [3]. Adults with elevated PTHrP showed a lower response to therapy with bisphosphonates, as PTHrP-related osteolysis could be decreased but not the PTHrP-related calcium-reabsorption of the kidney [1,22]. However, as calcitonin and pamidronate are potent therapy modalities with no severe adverse effects, the combination is also recommended in humoral hypercalcemia.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of intravenous ibandronate on levels of PTH-related protein during the hypercalcemia of malignancy was evaluated in 10 patients with cancer (40% female, age range 22-78 yrs). 16 Levels of PTH-related protein were measured before and for 6 days after receipt of a single dose of intravenous ibandronate 0.2-1.6 mg over 4 hours as part of a randomized controlled trial. Despite the decrease in serum calcium concentrations, no significant effect of ibandronate on PTH-related protein levels was noted.…”
Section: Human Pharmacodynamicsmentioning
confidence: 99%